Pengembangan Sistem Informasi Destinasi Wisata Pati berbasis Web Semantik - Nurkamid, Mukhamad; Fatah, Andrie Adzkia (Jurusan Teknologi Informasi Universitas Semarang, 2023)
The purpose of this study is to implement semantic web technology to search for tourist objects in Pati Regency using ontologies. Search engines are currently unable to provide the exact information that users need. While search engines that use semantics can provide relevant information because the data can be understood according to meaning and are interconnected. Ontology is used to store data in the form of objects that are interconnected with each other. The ontology approach was chosen as an alternative to current storage media (relational based), because the data is easier to present. Pati Regency has a lot of tourism potential to be developed. Statistical data on the number of tours in Pati every year has increased, including religious tourism, cultural tourism, nature tourism, educational tourism and industrial tourism. However, the existence of these many tours has not made the city of Pati a tourist destination for both local and foreign tourists. The results of this study are the presentation of data models for tourist destinations which include cultural tourism, educational tourism, nature tourism, historical tourism, industrial tourism, craft tourism and culinary tourism in Pati Regency which contains some information such as the name of the tour, type of tour, description, the location of the tour and the telephone of the tour.